Contratos de fornecimento know-how e a atuação do Instituto Nacional da Propriedade Industrial (INPI) no seu registro - Pirró, Vanessa (2017)
Know-how transaction is an important instrument for the dissemination of technical knowledge and strategic information, also operating as an important precedent for the generation of local innovations. This is a relatively recent subject which has not yet achieved institutional maturity in Brazil. Know-how does not have specific legal regulations, and a uniform definition of its concept is not verified. Given the peculiar characteristics of knowhow and its form of protection, the contracts that imply know-how transactions are complex, and must address essential clauses and other aspects that may have repercussions in its object. The purpose of this work is to discuss the importance of know-how transaction as a development tool as well as the specificities in contracts that deal with its transactions. In order to do so, we seek to approach the concept of know-how and related institutes, the elements that compose know-how, its legal nature and tutelage under Brazilian and international law. We also analyze the main elements of know-how contracts. A special chapter is dedicated to the specific regulation of know-how contracts by the Brazilian PTO (INPI), with an analysis of the historical context of its creation and the phases of its operation, addressing its present-day operation, which is still marked by an interfering position of the Institute